2015
DOI: 10.2337/dc14-1844
|View full text |Cite
|
Sign up to set email alerts
|

The Hemoglobin Glycation Index Identifies Subpopulations With Harms or Benefits From Intensive Treatment in the ACCORD Trial

Abstract: OBJECTIVEThis study tested the hypothesis that intensive treatment in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial disproportionately produced adverse outcomes in patients with diabetes with a high hemoglobin glycation index (HGI = observed HbA1c − predicted HbA1c).RESEARCH DESIGN AND METHODSACCORD was a randomized controlled trial of 10,251 patients with type 2 diabetes assigned to standard or intensive treatment with HbA1c goals of 7.0% to 7.9% (53 to 63 mmol/mol) and less than 6% (42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
193
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(211 citation statements)
references
References 43 publications
(59 reference statements)
11
193
3
4
Order By: Relevance
“…HGI represents a measure of the degree of non-enzymatic glycation of hemoglobin and it has been found to be positively associated with diabetic complications [21,22]. In patients with type 1 diabetes participating to the Diabetes Control and Complications Trial (DCCT) it has been observed that a higher HGI, calculated by using mean blood glucose levels, was associated with a greater risk of retinopathy and nephropathy [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HGI represents a measure of the degree of non-enzymatic glycation of hemoglobin and it has been found to be positively associated with diabetic complications [21,22]. In patients with type 1 diabetes participating to the Diabetes Control and Complications Trial (DCCT) it has been observed that a higher HGI, calculated by using mean blood glucose levels, was associated with a greater risk of retinopathy and nephropathy [21].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with type 1 diabetes participating to the Diabetes Control and Complications Trial (DCCT) it has been observed that a higher HGI, calculated by using mean blood glucose levels, was associated with a greater risk of retinopathy and nephropathy [21]. Furthermore, it has been recently reported that a higher HGI value, calculated by using fasting plasma glucose in patients with type 2 diabetes participating to the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial, was associated with diabetic complications and with greater mortality in the intensive treatment group [22]. However, whether HGI is associated with organ damage also in subjects without diabetes has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ACCORD, excess mortality was found in those who showed an increase in HbA 1c with intensive glucose control (39); thus, people with worsening glycemic control when exposed to intensive treatment should be set less stringent glucose targets. Additionally, intensive treatment was associated with improved primary outcomes in people with low and moderate hemoglobin glycation index (HGI) (HGI = observed HbA 1c 2 predicted HbA 1c ) but not with high HGI at baseline, and higher total mortality in intensively treated patients was confined to the high-HGI subgroup (40). A high HGI was also associated with greater risk for hypoglycemia (40).…”
Section: Hba 1c Targets In Specific Subgroupsmentioning
confidence: 99%
“…Additionally, intensive treatment was associated with improved primary outcomes in people with low and moderate hemoglobin glycation index (HGI) (HGI = observed HbA 1c 2 predicted HbA 1c ) but not with high HGI at baseline, and higher total mortality in intensively treated patients was confined to the high-HGI subgroup (40). A high HGI was also associated with greater risk for hypoglycemia (40). Finally, a retrospective subgroup analysis of the ACCORD data set, assessing the impact and tolerability of intensive glucose management in older versus younger adults ($65 vs. ,65 years), showed a 71% increased risk of cardiovascular mortality in the intensive arm for the younger subgroup (41).…”
Section: Hba 1c Targets In Specific Subgroupsmentioning
confidence: 99%